Pengaruh Keterbukaan Perdagangan dan IPM terhadap Pertumbuhan Ekonomi di Provinsi Jambi Periode 2014-2023 Dalam Tinjauan Maqashid Syariah - Luqyana Putri, Jihan; Zulgani, Zulgani; Dean Amri, Ary (ILTIZAM Journal of Shariah Economics Research, 2025)
This study aims to achieve two main objectives: (1) to examine both the partial and simultaneous effects of International Trade (Trade Openness) and the Human Development Index (HDI) on Economic Growth in Jambi Province during the period 2014–2023, and (2) to analyze Economic Growth, International Trade, and HDI from the perspective of Maqashid Sharia. This research adopts a quantitative approach using secondary time series data from 2014 to 2023, obtained from the official website of the Central Statistics Agency (BPS) of Jambi Province and other sources relevant to the research variables. The analytical method employed is multiple linear regression, supported by descriptive statistics and classical assumption tests. Data processing was conducted using EViews 12 software. The findings reveal that, simultaneously (based on the F-test), Trade Openness and HDI have a significant impact on Economic Growth in Jambi Province. In partial testing (t-test), Trade Openness shows a significant positive influence on economic growth, whereas HDI has a negative and statistically insignificant effect. From the perspective of Maqashid Sharia, Jambi Province is considered to have made notable progress in fulfilling the essential needs of its population. This is supported by data on economic growth as well as key indicators such as international trade performance and improvements in human quality, all of which align with Islamic principles